Case study on the influence of electrostatic charges on particle concentration in turbulent duct flows - Grosshans, H.; Villafañe, L.; Banko, A.; Papalexandris, M.V. (Powder technology, 2019)
Preferential concentration of inertial particles in wall-bounded turbulent flows is of paramount importance and, thus, subject of fundamental research. In practical applications of confined particle-laden flows the particles experience frequent collisions with the piping system which may result in an unwanted electric charge separation through triboelectric effects. The consequential occurrence of electrostatic forces alters the particle trajectories and their distribution. In this work the influence of charges on the averaged concentration of inertial particles in a fully developed turbulent duct flow was investigated by means of a combined numerical and experimental approach. The order of magnitude of the potential charge accumulation was estimated and imposed in a parametric study to the particulate phase in the simulations. Also, a new numerical approach based on the stochastic parcel method is introduced that allows to handle a large number of charged particles in a Lagrangian framework. This new approach extends standard formulations by including the effect of electrostatic forces on each parcel. The simulations demonstrate that the concentration profiles are for the most part independent of the prescribed charge except in the region close to the walls. The peaks of the particle number density at the walls caused by turbophoresis are strongly reduced through the local increase of repelling electrostatic forces. The comparison of numerical with experimental data indicates that the particles in the experimental setup could be affected by a surface charge density of the order of 100 C/m2. The presented results aim to elucidate the impact of electrostatic forces in the particle distribution in wall-bounded particle-laden flows.